Biotechnology for Wellness Industry: Concepts and Biofactories - Sarmidi, Mohamad R.; El Enshasy, Hesham A. (International Journal of Biotechnology for Wellness Industries, 2012)
One of the major issues in the 21st. century facing humankind is on how to stay healthy and delay the onset of chronic metabolic diseases. Chronic metabolic chronic diseases still afflict a substantial percentage of modern human population despite the advances in medical and health care technologies. They create a long-term financial burden to the nation as well as reducing the productivity and the quality of life. In the recent years, the wellness approach to healthy living by mean of health enhancement and disease prevention has been increasing in popularity. There is a tremendous global and local interest for wellness products. Wellness sector focuses on providing products and services to a wider community to improve appearance, slow down the effect of ageing and to reduce the risk of developing chronic metabolic diseases. The wellness products are intended for the promotion of health in soil, plants, animals and human. Soil health is the foundation of wellness as healthy and productive soil produce healthy plants and crops in turn produced healthy animals for human nutrition. It is a fact that human health is closely associated with the practice of healthy life style that include consuming wholesome nutrients, living in a non-toxic environment and enhancing physical and mental fitness. These factors in turn promote the attainment and maintenance of cellular homeostasis. Under cellular homeostasis the cellular metabolic activities are at their optimum. In this regard traditional and modern biotechnology offer comprehensive list of natural ingredients and metabolites essential for cellular metabolism. These natural ingredients and metabolites are derived from microbial, algal, plant, animals, and human sources. Most of these natural products are increasingly made available by using innovative bioprocess technologies as more of them are main components of functional foods, nutraceuticals, cosmeceuticals and therapeutics. Bioprocess industries are considered as source for both health and wealth. The new concept of bioprocess industries is based on using different types of cells as small micro-bio-factories. These small biofactories belong to different classes of living organisms ranging from the most primitive prokaryotic bacterial cells up to high eukaryotic human cells. In the present review, the concept of bioprocess design and cultivation of cells up to the industrial level will be presented.